The role of lactate to guide resuscitation - Debkumar Chowdhury (International Journal of Medical Research and Review, 2024)
’Doctor, this patient’s lactate is raised at 4mmol/l, do you want to prescribe some fluid?’’. There have been many a time where we as clinicians have had similar encounters in our clinical journey. The reaction would be to prescribe intravenous crystalloids, however with time and recent emphasis on the importance of damage control/source control resuscitation this has been realised to be fraught with errors. The approach differs if the resuscitation is a medical or trauma based. The aim of this article is to explore some of the concerns that the emergency and critical care clinicians have from a raised lactate.